A comparative study of the Dorper and Dorper X Red Maasai sheep - Inyangala, B.A.O.; Rege, J.E.O.; Itulya, S. (Research Inst. for Animal Husbandry, 1990)
Investigates environmental sources of variation influencing growth traits of the Dorper and Dorper X Red Maasai sheep with special reference to the relative performance of various geneotypes. Lamb traits studied were weights from birth to yearling and absolute growth rates between adjacent stages of growth.